2010
DOI: 10.1080/10810730.2010.522696
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk Perceptions, Beliefs, and Physician Avoidance in Appalachia: Results from the 2008 HINTS Survey

Abstract: Appalachians experience increased rates of cancer incidence and mortality and high-risk health behaviors. Additionally, Appalachians are often characterized by lower socioeconomic status, geographic isolation, and cultural beliefs such as fatalism. The purpose of this descriptive analysis is to identify cancer-related risk perceptions, beliefs, and physician avoidance behaviors among Appalachians as compared with non-Appalachians using data from the National Cancer Institute's 2008 Health Information National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 30 publications
3
83
1
Order By: Relevance
“…Other studies have examined the perceptions and attitudes of genetics, genetic testing, and genomic information of those at high-risk for breast cancer and Alzheimer's disease, women who were offered prenatal testing, African-American and EuropeanAmerican populations, as well as medical professionals, and consumers of genetic services (Lobb et al 2006;Hiraki et al 2009;Hines-Martin et al 2004;Etchegary et al 2008;O'Daniel et al 2010;Hernandez et al 2006). Although thoughts about cancer and vaccines have been addressed in the Appalachian population (Hutson et al 2007;Hutson et al 2011;Dorgan et al 2009;Vanderpool et al 2010), the topic of genetic research studies has not. Thus, our study fills this void in the literature and adds new information on the Appalachian population.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have examined the perceptions and attitudes of genetics, genetic testing, and genomic information of those at high-risk for breast cancer and Alzheimer's disease, women who were offered prenatal testing, African-American and EuropeanAmerican populations, as well as medical professionals, and consumers of genetic services (Lobb et al 2006;Hiraki et al 2009;Hines-Martin et al 2004;Etchegary et al 2008;O'Daniel et al 2010;Hernandez et al 2006). Although thoughts about cancer and vaccines have been addressed in the Appalachian population (Hutson et al 2007;Hutson et al 2011;Dorgan et al 2009;Vanderpool et al 2010), the topic of genetic research studies has not. Thus, our study fills this void in the literature and adds new information on the Appalachian population.…”
Section: Discussionmentioning
confidence: 99%
“…Participants who responded "yes" (n=2,327) were then asked to what extent they endorsed three researcher-identified reasons for avoiding the doctor (i.e., feeling uncomfortable when their body is being examined, fear of having a serious illness, and because it makes them think of dying); results concerning these items have been published elsewhere. 5,7,18,24 Next, participants were asked whether there were "any other reasons why you avoid seeing your doctor," and either wrote their response in a small box if completing a mail survey or stated their response to an interviewer, who summarized their response, if completing a phone survey. Responses were brief and typically consisted of a short phrase or sentence.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7] Even individuals with major health problems 4,8,9 or who are experiencing symptoms [10][11][12] avoid seeking medical care. For example, in one study, 17% of patients diagnosed with rectal tumors reported that they waited a year or more to seek medical consultation after noticing symptoms, with some waiting up to five years.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations